Design capabilities development in a Malaysian automotive vendor company - Ana Sakura, Zainal Abidin; Rasli, Muslimen; Shahrol, Mohamaddan; Rosnah, Mohd Yusuff; Noorul Amni Qistina, Mohd Daud (2015)
Global competition has made manufacturing enhancement saturated. Manufacturers have to find new ways of increasing their competitiveness. A company's capability to conduct design determines the success of innovative products as a main determinant of profit attainment, especially in the technological industry. Design capability (DC) is defined as the availability of technical manpower skills and facilities to conduct design, namely, R&D, testing equipment and prototyping facilities, and the presence of technology to support current and future manufacturing innovations. DC is a company unique resource and can be deployed as a strategy to response in any circumstances and enable a company to anticipate future market demands and to manage global challenges. However, not many Malaysian automotive vendors have full in-house DC. Prior studies also found that Malaysian vendors have limited capabilities in finance, technology and facilities which have impeded the DC development. There is a number of critical success factors (CSFs) involved in developing successful DC. Currently, studies on vendors DC, particularly in Malaysia are very limited, making the development process more complicated. A study was conducted in an automotive vendor company that has successfully developed an in-house DC and was able to improve its business performance. Productivity, reputation and the company's competitive advantage were increased. Thus, the DC development of the company was studied and a framework was proposed. This study is to enable other vendor companies to emulate and understand the DC requirements and serve as a guide for other companies intending to develop their DC.